Oral health status in 12 to 17-year-old school children from Valle Nonguén, Concepción, 2013. - Ivania Contreras; Estefanía Contreras; Pamela Araneda; Beatríz Solís (Universidad de Concepción., 2013)
Dental caries, periodontal disease and dento-maxillary anomalies are the most common oral problems both globally and nationally. The aim of this study is to determine the oral health status in terms of caries damage, oral hygiene and dento-maxillary anomalies, and their relationship with socio-demographic factors in school children from Valle Nonguén sector, whose ages fluctuate from 12 to 17 years old. This is a study of prevalence which was conducted on a sample of 210 school children, the following indexes were utilized: DMFT, Simplified Oral Hygiene Index (OHI-S), and Dental Aesthetic Index (DAI), sex, age and type of educational establishment (public/subsidized). The results showed that 94.76% of the students have caries damage with a DMFT average of 6.87±3.42, higher in women and adolescents aged 16-17; 73.57% of them have a regular hygiene, with OHI-S higher in 14-15-year-old adolescents and public schools, and a 75.2% has at least one manifest malocclusion (19.05% in a disabling level). These results show that the 12-17-year-old students from Valle Nonguén have a high rate of oral disease in all indexes, higher than national and international studies. A priority is to design and implement preventive/healing dental programs in this group. These results question the design and possible impact of the new program "FONASA Libre Elección 12-17 años" in neighborhoods with limited resources and high treatment needs.